Phụ thuộc hàm trong cơ sở dữ liệu quan hệ mở rộng - Thanh, Đinh Thị Ngọc (Journal of Computer Science and Cybernetics, 2016)
We introduced some constraints of incomplete data in the extended relational database by theory of linguistic variable and fuzzy sets. The constraints have a structure as well as functional dependencies. The same results of minimum cover and 3NF of relation are given in the extended RDB.